Integrated Agricultural Development in High-Altitude Tribal Areas: A Participatory Watershed Programme in the East Indian Himalaya. (June 2013) - Das, Anup; Munda, G.C.; Thakur, N.S. Azad; Lal, B.; Ghosh, P.K.; Ngachan, S.V.; Bujarbaruah, K.M.; Yadav, R.K.; Mahapatra, B.K.; Das, S.K.; Dutta, K.K.
A high-altitude (> 1, 500 m asl) integrated participatory watershed development programme was implemented between 2004 and 2008 in the West Khasi Hills, Meghalaya, North-Eastern Indian Himalaya. The aim was to assess and refine practices for integrating crop, fish and livestock production systems. Soil and water conservation measures, with the active participation of local inhabitants, included the construction and renovation of ponds, jalkunds (micro rainwater-harvesting structures) and bench and half-moon terraces. Impact analysis revealed that 4.3 million litres of water were harvested and enhanced potato and rice crop productivity by 30% to 40% and 45% to 50% respectively. Farmers are now able to earn net incomes of around 56.8 and 8.9 per month from community dairy units and fish ponds respectively.